The Effectiveness of Desensitizing Agents for Treating Dentin Hypersensitivity: A Meta-Analysis (Bangladesh Journal of Medical Science, 2026)
Dentin hypersensitivity (DH) affects 10–30% of adults, causing sharp pain from exposed dentin. Despite various treatments, efficacy comparisons remain unclear. This meta-analysis aimed to evaluate the effectiveness of desensitizing agents for DH. Following PRISMA guidelines, 30 RCTs were analyzed. Databases included PubMed, Embase, and Cochrane. Outcomes were pain reduction (VAS, Schiff scale) and tubule occlusion (SEM). Random-effects models calculated pooled effect sizes. Bioactive materials (e.g., bioactive glass) showed the strongest effects (40–60% pain reduction), followed by arginine (50–70%). Lasers and SDF provided rapid relief but had limitations (cost, side effects). At-home treatments (e.g., stannous fluoride) offered moderate efficacy (30–50%). Heterogeneity was low (I² = 22.43%), and publication bias was minimal. Desensitizing agents are effective for DH, with bioactive materials and combination therapies yielding optimal results. Clinicians should tailor treatments based on patient needs and agent availability.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S63-S77